2007
DOI: 10.1177/1056789506067935
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Between Mesoplasticity and Damage in High-cycle Fatigue

Abstract: ABSTRACT:The multiaxial fatigue loading in the high-cycle regime leads to localized mesoscopic plastic strain that occurs in some preferential directions of individual grains for most metallic materials. Crack initiation modeling is difficult in this fatigue regime because the scale where the mechanisms operate is not the engineering scale (macroscopic scale), and local plasticity and damage act simultaneously. This article describes a damage model based on the interaction between mesoplasticity and local dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Different continuum damage mechanics based models have been proposed in the literature for the high-cycle fatigue analysis of metallic structures. Among others, models based on two-scale approaches in which micro and mesoscales are linked by means of a localization law (Lemaitre and Doghri, 1994;Lemaitre et al, 1999;Desmorat and Lemaitre, 2001;Lemaitre and Desmorat, 2005;Desmorat, 2006;Desmorat et al, 2007;Flaceliere et al, 2007aFlaceliere et al, , 2007b, and models relying on a single macroscopic (engineering) scale (Oller et al, 2005;Ottosen et al, 2008) can be found in the fatigue of metals literature. However, due to its inherent multi-scale manifestation, the high-cycle fatigue damage can only be properly captured by resorting to models which are capable of dealing with plasticity and damage on a scale smaller than the macroscopic scale, as for instance the two-scale models cited above.…”
Section: Introductionmentioning
confidence: 99%
“…Different continuum damage mechanics based models have been proposed in the literature for the high-cycle fatigue analysis of metallic structures. Among others, models based on two-scale approaches in which micro and mesoscales are linked by means of a localization law (Lemaitre and Doghri, 1994;Lemaitre et al, 1999;Desmorat and Lemaitre, 2001;Lemaitre and Desmorat, 2005;Desmorat, 2006;Desmorat et al, 2007;Flaceliere et al, 2007aFlaceliere et al, , 2007b, and models relying on a single macroscopic (engineering) scale (Oller et al, 2005;Ottosen et al, 2008) can be found in the fatigue of metals literature. However, due to its inherent multi-scale manifestation, the high-cycle fatigue damage can only be properly captured by resorting to models which are capable of dealing with plasticity and damage on a scale smaller than the macroscopic scale, as for instance the two-scale models cited above.…”
Section: Introductionmentioning
confidence: 99%
“…This original critical plane model is derived from a previous approach based on a Von Mises type plasticity rule to model the fatigue behaviour of a group of average grains 21 …”
Section: A Critical Plane Approach Based On Coupled Mesoplasticity Anmentioning
confidence: 99%
“…This original critical plane model is derived from a previous approach based on a Von Mises type plasticity rule to model the fatigue behaviour of a group of average grains. 21 The goal of the new model is to reflect the salient features of the mesoscopic behaviour of the crystal. The assumptions are:…”
Section: A C R I T I C a L P L A N E A P P R O A C H B A S E D O N C mentioning
confidence: 99%
“…(2009)and Papuga (2011). Three categories of models are usually used: critical plane-based models (Carpinteri and Spagnoli, 2001; Carpinteri et al., 2003, 2014b; Papuga and Ruzicka, 2008; Shang et al., 2007; Shang and Wang, 1998; Susmel and Lazzarin, 2002; Zhang and Yao, 2011; Zhang et al., 2018), mesoscopic scale-based models (Brünig et al., 2011; Flaceliere et al., 2007; Eslami et al., 2016; Ju and Ko, 2008; Shariyat, 2010; Tay et al., 2008) and energy-based models (Ahmadzadeh and Varvani-Farahani, 2016; Chen et al., 1999; Zhu et al., 2012, 2017). Since the critical plane method has physical meaning, it is widely used in service.…”
Section: Introductionmentioning
confidence: 99%